2022
DOI: 10.1136/jitc-2022-005333
|View full text |Cite
|
Sign up to set email alerts
|

Efficient preclinical treatment of cortical T cell acute lymphoblastic leukemia with T lymphocytes secreting anti-CD1a T cell engagers

Abstract: BackgroundThe dismal clinical outcome of relapsed/refractory (R/R) T cell acute lymphoblastic leukemia (T-ALL) highlights the need for innovative targeted therapies. Although chimeric antigen receptor (CAR)-engineered T cells have revolutionized the treatment of B cell malignancies, their clinical implementation in T-ALL is in its infancy. CD1a represents a safe target for cortical T-ALL (coT-ALL) patients, and fratricide-resistant CD1a-directed CAR T cells have been preclinically validated as an immunotherape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(56 reference statements)
2
7
0
Order By: Relevance
“…CD1a, a cell surface antigen, is specifically expressed in coT-ALL and retained in relapsed coT-ALL, but barely expressed in normal cells/tissues. CD1a-specific CAR-T therapy has been validated preclinically for relapsed/refractory coT-ALL [ 59 ]. A recent phase II clinical trial of anti-CD1a CAR-T in treating R/R T-ALL was initiated (NCT05745181).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD1a, a cell surface antigen, is specifically expressed in coT-ALL and retained in relapsed coT-ALL, but barely expressed in normal cells/tissues. CD1a-specific CAR-T therapy has been validated preclinically for relapsed/refractory coT-ALL [ 59 ]. A recent phase II clinical trial of anti-CD1a CAR-T in treating R/R T-ALL was initiated (NCT05745181).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it is challenging to achieve sufficient effector T cells from relapsed/refractory patients owing to the aggressiveness and hyper leukocytic of the disease. A study suggests that engineered T cells secreting CD1a XCD3 T-cell-engaging antibodies (CD1a-STAb) may be applied for coT-ALL patients with limited numbers of effector T cells [ 59 ]. This study showed that CD1a-T-cell engagers induce specific T-cell activation through binding to CD1a and CD3 on the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…First evidence of efficacy has recently been shown in phase I clinical trials of novel CAR T-cell products targeting CD30 in Hodgkin lymphoma 23 and CD7 in T-ALL, 24-26 with additional products for T-ALL under investigation. 27-29 Objective responses now also support the general promise of CAR T-cell targeting in pediatric solid cancers. 30-33 CAR T-cell therapy has been reported to be beneficial in diffuse intrinsic pontine gliomas, a cancer with a very poor prognosis, 32 and complete and even durable remissions have been obtained in neuroblastoma.…”
mentioning
confidence: 92%
“…Sustained in vivo TCE secretion results in effective serum concentrations of the TCE (28). Furthermore, expansion and persistence of adoptively transferred STAb-T cells (29,30), as well as polyclonal recruitment of both genemodified STAb-T cells and unmodified bystander T cells to the tumor microenvironment (TME), can lead to substantially increased antitumor responses (29)(30)(31). The therapeutic potential of STAb-T cells has been demonstrated in B cell (29)(30)(31)(32) and T cell hematological malignancies (30).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expansion and persistence of adoptively transferred STAb-T cells (29,30), as well as polyclonal recruitment of both genemodified STAb-T cells and unmodified bystander T cells to the tumor microenvironment (TME), can lead to substantially increased antitumor responses (29)(30)(31). The therapeutic potential of STAb-T cells has been demonstrated in B cell (29)(30)(31)(32) and T cell hematological malignancies (30). Here, we report the generation of STAb-T cells secreting an anti-BCMA TCE and demonstrate their superior efficacy over BCMA-specific CAR-T cells under T cell-limiting conditions simulating those found in patients with multitreated MM.…”
Section: Introductionmentioning
confidence: 99%